1963
DOI: 10.1139/v63-462
|View full text |Cite
|
Sign up to set email alerts
|

N.M.R. Studies of Bridged Ring Systems. I. Carbon-Hydrogen Spin Coupling Constants in Bicyclo[2,2,1]heptane Derivatives

Abstract: which mas previously evacuated and weighed. The flask was then filled with dry ether to precipitate the salt and placed in the refrigerator overnight. The liquor was decanted using an aspirator, but enough was left behind to keep the crystals covered. The remaining liquid was removed under vacuum. The white salt was then dried over phosphorous pentoxide under vacuum. a -P h e n e t h~ ldimethylsulphoniurn bromide-reaction time 96hours; yield 10.17,; 1n.p. 91.7-92.8" C (lit. 1n.p. 76-80" C ref. ( 8 ) N.M.R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Additional long-range spin couplings, if they appear, will be small (3, 8,11). The geminal coupling constant of these bridge methylene protons is believed to be about 8 c.p.s., which is unusually small, by reference to this sort of the coupling constant in V (20). The differences in the chemical shifts between the protons H, and H, on the ethylene bridge of I1 and IV should be much larger than the value observed in I , because of the anisotropy effect of a double bond or a benzene ring.…”
Section: And Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Additional long-range spin couplings, if they appear, will be small (3, 8,11). The geminal coupling constant of these bridge methylene protons is believed to be about 8 c.p.s., which is unusually small, by reference to this sort of the coupling constant in V (20). The differences in the chemical shifts between the protons H, and H, on the ethylene bridge of I1 and IV should be much larger than the value observed in I , because of the anisotropy effect of a double bond or a benzene ring.…”
Section: And Discussionmentioning
confidence: 83%
“…of C-C bonds of 111 and V with the "bent" of the bonds due to the Inore ring strain, as reflected in the increased JC13-R values in the rings (20). The signal of the bridge methylene of VI also appears a t a very low field as 7.987, as shown in Table I.…”
Section: Unusual Deshielding Effects U P O N Bridge Methytenes Of Normentioning
confidence: 89%
See 1 more Smart Citation
“…Nuclear magnetic resonance studies have shown that this bridgehead bond has a much higher degree of s-character than is found in a normal sp3 bond (25). All other hydrogen atoms of the bicycloheptadiene molecule are liltely to show low reactivity towards metathesis, but the double bonds are reactive towards the addition of free radicals in general, and the ethyl radical in particular.…”
Section: Ring Conformation and Reactivitymentioning
confidence: 96%
“…But the success of BEBO formalism merits further attention. One wonders whether the quantum chemical bond order or some other property of the bond being broken or formed would generally reveal some "exalted" features when examined along the reaction path.30 If the answer (5) Mayer, S. W.; Schieler, L; Johnston, H. Table II. Variation in the Computed Hydrogen Free Valence Index (fH) along the Photodissociation Path of HNO (3A")°- Figure 1 shows the section of the potential energy surface along the reaction path for the isomerization of HNO to NOH in the lowest 3A" state.…”
Section: Subunitmentioning
confidence: 99%